Oral Hygiene and Cardiovascular Health - Md S. Zaman; S. M. Golam Alam; Mohammed S. Razzaque (Hygiene, 2025)
The human oral microbiome plays a vital role in maintaining oral and systemic health. This diverse microbial community includes over 700 bacterial species, some of which are implicated in developing systemic diseases, particularly cardiovascular diseases (CVDs). Research highlights a strong association between periodontal disease and increased cardiovascular risk, suggesting that good oral hygiene practices may reduce the incidence of CVDs. Porphyromonas gingivalis and Fusobacterium nucleatum drive chronic inflammation in periodontal disease; these bacteria can extend beyond the mouth and contribute to systemic inflammatory responses. The inflammatory factors, including C-reactive protein (CRP), interleukins (IL-1, IL-6), and tumor necrosis factor-alpha (TNF-α), damage blood vessels, impair endothelial functions, and promote atherosclerosis, all key events in CVD progression. Additionally, oral pathogens may accelerate plaque formation in arteries, increasing the risk of ischemic heart and brain diseases. Studies show a 28% increased risk of heart disease in individuals with periodontal disease. Treating periodontal disease can improve endothelial function and reduce inflammatory markers, emphasizing oral health management as a potential preventive strategy for CVD. Public health initiatives that emphasize oral hygiene and early periodontal disease treatment are crucial for broader cardiovascular care.